Pigmented lesion in hard palate: a graphite tattoo - Molini, Patricia Roccon Bianchi; Velloso, Tânia Regina Grao; Silva, Daniela Nascimento; Bertollo, Rossiene Motta; Azevedo, Sergio Lins Vaz de; Pereira, Teresa Cristina Rangel; Barros, Liliana Aparecida Pimenta de (Journal of Oral Diagnosis, 2016)
Oral pigmented lesions are commonly noted in odontologic practice. Clinical features of malignant and benign lesions show enough similarity that makes clinical differentiation difficult or impossible. Exogenous pigmentations in orign are usually due to a foreign-body implantation in the oral mucosa and the graphite as an exogenous source of pigmentation in the oral cavity has been reported sporadically. This report is presents a case of a graphite tattoo in hard palate of a young female adult and discusses the diferential diagnosis with blue nevus and early oral melanoma. It reinforces that oral pigmented lesions must be carefully evaluated and a malignant lesion should not be ignored until a final diagnosis be established.